Hybrid catalyst system for producing multimodal elastomers

CN122978337APending Publication Date: 2026-10-27DOW GLOBAL TECHNOLOGIES LLC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202610905065.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-07-29
Filing Date
2017-07-25
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,需要控制多峰弹性体,使得它们不具有大量的长链支化和高粘度,这在将多峰弹性体共混到TPO中时可能是有害的

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978337A_ABST
    Figure CN122978337A_ABST
Patent Text Reader

Abstract

Embodiments of the present disclosure relate to the production of multi-modal elastomers by the polymerization of olefins with a mixed catalyst system, specifically a constrained geometry catalyst and a biphenol catalyst. The multi-modal elastomers can be incorporated as impact modifiers in thermoplastic olefins.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of Chinese patent application No. 201780045722.0 (filed on July 25, 2017, entitled "Mixed Catalyst System for Generating Multimodal Elastomers"). Technical Field

[0002] Embodiments of this disclosure relate to multimodal elastomers, and more particularly to multimodal polyolefin elastomers produced by olefin polymerization using a mixed catalyst system. Background Technology

[0003] Olefin-based elastomers, including ethylene and α-olefins, are produced through various catalyst systems. The choice of this catalyst system used in the polymerization of olefin-based polymers is a crucial factor contributing to the properties and characteristics of these polymers. Many different polymers and materials have been added to polymer formulations to enhance or maintain impact strength while improving other properties. For example, thermoplastic olefins (TPOs) are commonly used in polymer formulations due to their desirable impact strength properties.

[0004] TPO is typically made from blends of elastomeric materials such as ethylene-based random copolymers, ethylene / propylene rubber (EPM), or ethylene / propylene diene monomer terpolymers (EPDM), and stiffer materials such as isotactic polypropylene. Depending on the application, other materials or components may be added to the formulation, including fillers such as talc. TPO is generally characterized by a balance between stiffness (modulus) and low-temperature impact, as well as a wide operating temperature range. TPO is commonly injection molded into articles for use in many applications, including automotive bumper panels, dashboards, pillars, and airbag covers. For TPO compounds, the desired viscosity is one that allows for easy filling relative to the intended use, as well as improved flowability over long, thin flow paths.

[0005] Multimodal elastomers are effective impact modifiers for TPO. However, it is necessary to control the multimodal elastomers to avoid excessive long-chain branching and high viscosity, which can be detrimental when blending them into TPO. Therefore, improvements in multimodal elastomers and their preparation methods are likely to remain needed. Summary of the Invention

[0006] The embodiments of this disclosure satisfy this need by using a mixed catalyst system, specifically a geometry-defined catalyst and a biphenol catalyst, to produce multimodal elastomers via olefin polymerization. The high molecular weight fraction of the multimodal elastomer products of this disclosure can be effectively used as impact modifiers, but their low shear viscosity is sufficient for blending in TPO.

[0007] According to one embodiment of this disclosure, a multimodal elastomer comprises a copolymer of ethylene and at least one α-olefin comonomer, wherein the multimodal elastomer comprises: 20% to 90% by weight of a high molecular weight (HMW) fraction, wherein the number average molecular weight (Mn) of the HMW fraction is at least 50 kg / mol when measured by gel permeation chromatography (GPC), and wherein the HMW fraction comprises at least 35% by weight of ethylene and at least 30% by weight of the α-olefin comonomer; and a low molecular weight (LMW) fraction, wherein the Mn of the LMW fraction is from 4 kg / mol to 25 kg / mol, and wherein the LMW fraction comprises at least 50% by weight of ethylene and at least 29% by weight of the α-olefin comonomer, and the ratio of the Mn of the HMW fraction to the Mn of the LMW fraction is at least 5:1; wherein the density of the multimodal elastomer is between 0.853 g / cc and 0.875 g / cc, and the shear viscosity at 100 rad / s is less than 2,500 g / cc. Pa-s, and a shear viscosity of less than 120,000 Pa-s at 0.1 rad / s.

[0008] Other embodiments involve thermoplastic olefins comprising the multimodal elastomer and polypropylene.

[0009] According to a method for preparing the multimodal elastomer, the method includes: adding at least one ethylene monomer, at least one α-olefin comonomer, a first catalyst comprising a biphenol complex, and a second catalyst comprising a complex with a defined geometry to a reactor system comprising one or more reactors. The method further includes: producing the multimodal elastomer by solution polymerization at a temperature of at least 100°C. The multimodal elastomer comprises a high molecular weight (HMW) fraction and a low molecular weight (LMW) fraction, wherein the number average molecular weight (Mn) of the HMW fraction is at least 50 kg / mol when measured by gel permeation chromatography (GPC), and wherein the HMW fraction comprises at least 35 wt% ethylene and at least 30 wt% of the α-olefin comonomer, and wherein the Mn of the LMW fraction is from 4 kg / mol to 25 kg / mol, and wherein the LMW fraction comprises at least 50 wt% ethylene and at least 29 wt% of the α-olefin comonomer. Furthermore, the multimodal elastomer comprises: a ratio of Mn in the HMW fraction to Mn in the LMW fraction of at least 5:1; a density between 0.853 g / cc and 0.875 g / cc; a shear viscosity of less than 2,500 Pa·s at 100 rad / s; and a shear viscosity of less than 120,000 Pa·s at 0.1 rad / s shear.

[0010] Additional features and advantages of the embodiments will be set forth in the following detailed description and claims, and to some extent, these features and advantages will be apparent or recognized by those skilled in the art from the detailed description or by practice of the embodiments described herein. Attached Figure Description

[0011] It should be understood that both the foregoing and the following description describe various embodiments and are intended to provide an overview or framework for understanding the nature and characteristics of the claimed subject matter. The accompanying drawings are included to provide a further understanding of the various embodiments and are incorporated in and form a part of this specification. The drawings illustrate the various embodiments described herein and, together with the implementation methods, serve to explain the principles and operation of the claimed subject matter.

[0012] Figure 1 These are GPC curves depicting data of multi-peak and single-peak elastomers according to one or more embodiments of this disclosure.

[0013] Figure 2 This is a diagram illustrating the dynamic mechanical spectroscopic (DMS) rheological data of multi-peak and single-peak elastomers according to one or more embodiments of the present disclosure at 190°C. Detailed Implementation

[0014] Embodiments of this disclosure relate to a multimodal elastomer comprising a copolymer of ethylene and at least one α-olefin comonomer.

[0015] As used herein, the term “multi-peak” refers to a gel permeation chromatography (GPC) curve in which the molecular weight distribution (MWD) exhibits two or more component polymers, for example, two or more peaks, or even one component polymer may present as a hump, shoulder, or tail peak relative to the MWD of other component polymers.

[0016] In one or more embodiments of this disclosure, the multimodal elastomer may be a bimodal elastomer. As used herein, the term "bimodal" refers to a GPC curve in which the MWD exhibits two component polymers, wherein one component polymer may even have a hump, shoulder, or tail peak relative to the MWD of the other component polymers. The bimodal MWD can be deconvoluted into two main components: a polymer fraction based on high molecular weight (HMW) ethylene and a polymer fraction based on low molecular weight (LMW) ethylene. As further described below, according to the GPC, the HMW fraction may have a higher number-average molecular weight (Mn) and a higher or lower α-olefin comonomer content than the LMW fraction. After deconvolution, the Mn and weight-average molecular weight (Mw) of each component can be obtained.

[0017] Multimodal elastomers

[0018] In one or more embodiments, the multimodal elastomer may comprise 20 wt% to 90 wt% of an HMW fraction, wherein the Mn of the HMW fraction is at least 50 kg / mol when measured according to GPC. In another embodiment, the multimodal elastomer may comprise 30 wt% to 90 wt%, or 50 wt% to 85 wt%, or 50 wt% to 70 wt% of an HMW fraction. Furthermore, in another embodiment, the Mn of the HMW fraction may be greater than 75 kg / mol, or greater than 100 kg / mol, or greater than 150 kg / mol, or greater than 200 kg / mol. In other words, suitable ranges for the molecular weight of the HMW fraction include 50 kg / mol to 600 kg / mol, or 100 kg / mol to 400 kg / mol, or 150 kg / mol to 300 kg / mol.

[0019] Multimodal elastomers may include an LMW fraction with Mn ranging from 4 kg / mol to 25 kg / mol. In other embodiments, the LMW fraction may be 5 kg / mol to 25 kg / mol, or 7 kg / mol to 25 kg / mol, or 10 kg / mol to 20 kg / mol. Furthermore, the multimodal elastomer may contain 10 wt% to 70 wt%, or 20 wt% to 60 wt%, or 30 wt% to 50 wt% of an LMW fraction.

[0020] In one or more embodiments, the ratio of Mn in the HMW fraction to Mn in the LMW fraction is at least 5:1, or at least 8:1, or at least 10:1. Without being bound by theory, the higher Mn in the HMW fraction and the lower Mn in the LMW fraction ensure that the multimodal elastomer can improve the impact modification properties of TPO, while also ensuring good processability when blended in TPO and during the TPO process, such as injection molding. The impact modification properties of the multimodal elastomer can be largely attributed to the higher Mn in the HMW fraction, while the processing benefits of the multimodal elastomer are primarily attributed to the LMW fraction. As will be further explained below, the mixed catalyst system induces the desired Mn variation between the LMW and HMW fractions.

[0021] As mentioned above, multimodal elastomers include ethylene and α-olefin comonomers in polymeric form. Suitable α-olefin comonomers can contain 3 to 20 carbon atoms (C3-C4). 20 Those of which. In some embodiments, α-olefins may be C4-C. 20 α-olefins, C4-C 12 α-olefins, C3–C 12 α-olefins, C3–C 10α-olefins, C3–C8 α-olefins, C4–C8 α-olefins, or C6–C8 α-olefins. In some embodiments, the α-olefin comonomer is selected from the group consisting of propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-heptene, 1-octene, 1-nonene, and 1-decene. In a specific embodiment, the α-olefin comonomer is 1-octene.

[0022] Various levels of α-olefin comonomer incorporation are envisioned for both the HMW and LMW fractions. As discussed further below, the degree of α-olefin comonomer incorporation depends on the mixed catalyst system used, i.e., a defined geometry complex (CGC) catalyst that primarily drives the olefin polymerization of the LMW fraction and a bisphenylphenol (BPP) catalyst that primarily drives the olefin polymerization of the HMW fraction. In one or more embodiments, the HMW fraction may include at least 30 wt% or at least 40 wt% of α-olefin comonomer. In other embodiments, the LMW fraction may include at least 29 wt% or at least 35 wt% of α-olefin comonomer. In still other embodiments, both the HMW and LMW fractions may each contain less than 50 wt% of α-olefin comonomer.

[0023] Various doping levels are also envisioned for the HMW fraction. For example, the HMW fraction may contain at least 35% by weight of ethylene monomer, or at least 50% by weight of ethylene monomer, or at least 60% by weight of ethylene monomer, or at least 70% by weight of ethylene monomer. In other embodiments, the LMW fraction may contain at least 50% by weight of ethylene monomer, or at least 60% by weight of ethylene monomer, or at least 70% by weight of ethylene monomer.

[0024] In another embodiment, the weight percentage of α-olefin comonomer incorporated into the HMW fraction is greater than the weight percentage of α-olefin comonomer incorporated into the LMW fraction. Furthermore, the weight percentage of α-olefin comonomer in the HMW fraction is at least 4% by weight, or at least 5% by weight, or at least 10% by weight, or at least 15% by weight greater than the weight percentage of α-olefin comonomer in the LMW fraction. Although multimodal elastomers can be produced in a single reactor or a dual reactor, a dual reactor system can achieve a greater difference between the amount of α-olefin comonomer incorporated into the HMW fraction and the amount incorporated into the LMW fraction.

[0025] In one or more embodiments, the density of the multimodal elastomer may be less than 0.900 g / cc as measured according to ASTM D792. In other embodiments, the density of the multimodal elastomer is between 0.850 g / cc and 0.880 g / cc, or 0.853 g / cc and 0.875 g / cc, or 0.860 g / cc and 0.875 g / cc.

[0026] To demonstrate the required rheological properties and processability, the shear viscosity of the multimodal elastomer can be less than 120,000 Pa·s, or less than 90,000 Pa·s, or less than 60,000 Pa·s at 0.1 rad / s (V0.1), and less than 2500 Pa·s, or less than 2000 Pa·s, or less than 1200 Pa·s at 100 rad / s (V100). To reiterate, the aforementioned multimodal elastomer will provide the required dispersion rheology and injection molding processability for TPO, as demonstrated by the low and high shear viscosities.

[0027] Methods for preparing multi-peak elastomers

[0028] As described above, multimodal elastomers are produced via a mixed catalyst system for olefin polymerization. As used herein, “mixed catalyst” refers to the use of a combination of catalysts, specifically defining a geometry complex (CGC) catalyst and a biphenol (BPP) catalyst; however, there is no requirement to blend the CGC and BPP catalysts together or even include them in the same reactor. Multimodal elastomers can be produced by any number of methods, contained in situ in a single reactor or a series of cascade reactors, or blended via post-reactor processes. Various polymerization processes can be employed, such as solution polymerization using one or more conventional reactors, including parallel, series loop reactors, isothermal reactors, stirred tank reactors, batch reactors, and / or any combination thereof.

[0029] In one embodiment, a method for preparing a multimodal elastomer includes adding ethylene monomer and at least one α-olefin comonomer to a reactor system in the presence of a biphenol (BPP) complex catalyst and a defined geometry complex (CGC) catalyst, and then performing solution polymerization at a temperature of at least 100°C to produce the multimodal elastomer. As used herein, a “reactor system” can refer to a single reactor or multiple reactors connected in series or in parallel. In a single-reactor embodiment, ethylene, at least one α-olefin comonomer, and CGC and BPP catalysts are added to a single reactor, and solution polymerization is performed in that single reactor to produce the multimodal elastomer. Various reaction methods are contemplated in dual-reactor embodiments. For example, it is contemplated that the reactors can be arranged in parallel such that ethylene, at least one α-olefin comonomer, and BPP catalyst are used to produce the HMW fraction in one reactor, while ethylene, at least one α-olefin comonomer, and CGC catalyst are used to produce the LMW fraction in a second reactor. Subsequently, the LMW and HMW fractions are combined in one of the reactors to produce the multimodal elastomer.

[0030] Various embodiments for CGC catalysts are envisioned. As is well known to those skilled in the art, a defined geometry catalyst is a multi-component catalyst system comprising a CGC pre-catalyst and a co-catalyst, as well as other optional components. As used herein, a CGC pre-catalyst can be described as having a metal coordination complex comprising a metal from Groups 3 to 10 or a lanthanide element of the periodic table and a delocalized n-bonded moiety with restricted induced partial substitution. The complex has a defined geometry surrounding the metal atom such that the metal angle between the centroid of the delocalized substituted n-bonded moiety and the center of at least one remaining substituent is smaller than that in similar complexes containing a similar n-bonded moiety lacking in such restricted induced substituents.

[0031] Furthermore, the pre-CGC catalyst can be defined by a metal complex of Formula I:

[0032] (Formula I)

[0033] in

[0034] M CGC It refers to metals in groups 3 to 10 or lanthanides in the periodic table; Cp* is bonded to M via η5 bonding. CGC Bonded cyclopentadienyl or substituted cyclopentadienyl;

[0035] Z CGC It includes the portion containing boron, or is a member of Group 14 of the periodic table;

[0036] X CGCEach occurrence independently is an anionic ligand group or a neutral Lewis base ligand group with up to 30 non-hydrogen atoms; n is 0, 1, 2, 3, or 4, and is more than M CGC Its valence is less than 2; and

[0037] Y CGC Is with Z CGC and M CGC Bonded anionic or non-anionic ligand groups, including nitrogen, phosphorus, oxygen or sulfur and having up to 20 non-hydrogen atoms.

[0038] The cocatalyst is often referred to as an activating cocatalyst because the complex of formula (I) can be activated by combination with one or more cocatalysts, such as a cationic cocatalyst, a strong Lewis acid, or a combination thereof. Suitable cocatalysts may comprise alkylaluminum, polymeric or oligomeric aluminum oxanes, and inert, compatible, noncoordinated ion-forming compounds. Examples of polymeric or oligomeric aluminum oxanes may include methylaluminoxane, triisobutylaluminum-modified methylaluminoxane, and isobutylaluminoxane. In one or more specific embodiments, exemplary suitable cocatalysts may comprise, but are not limited to, modified methylaluminoxane (MMAO), bis(hydrogenated tallow alkyl)methyl, tetra(pentafluorophenyl)borate (1-)amine (RIBS-2), or combinations thereof.

[0039] Further details and examples of CGC catalysts are provided in U.S. Patent Nos. 5,272,236, 5,278,272, 6,812,289 and WO Publication 93 / 08221, all of which are incorporated herein by reference in their entirety.

[0040] Various embodiments have also been envisioned for diphenylphenol (BPP) catalysts. Similar to CGC catalysts, BPP catalysts are multi-component catalyst systems comprising a co-catalyst and an activating co-catalyst, as well as additional optional components. The BPP pre-catalyst may comprise a metal complex as shown in Formula II below:

[0041] (Formula II)

[0042] Where M BPP It is titanium, zirconium, or hafnium, each independently in an oxidation state of +2, +3, or +4; and n is an integer from 0 to 3, where when n is 0, X does not exist. BPP And each X BPP Independently, it is a neutral, monoanionic, or bis-anionic monodentate ligand; or two X... BPP Together they form neutral, monoanionic, or bis-anionic bidentate ligands; and select X BPP and n, such that the metal-ligand complex of formula (I) is generally neutral; and each Z BPPIndependently O, S, N (C1-C 40 ) hydrocarbon group or P(C1-C 40 ) hydrocarbon group; and L is (C2-C 40 ) hydrocarbon group or (C2-C 40 ) heterohydrocarbon group, of which (C2-C 40 The alkylene group has a portion of the main chain consisting of 2-carbon atoms to 10-carbon atoms, including the Z atom in the linking formula (I) (with L bonds attached thereto), and (C2-C 40 The heteroalkyl group has a portion of the connecting backbone consisting of 3- to 10-atoms of the Z atom in the connecting formula (I), wherein (C2-C 40 The 3 to 10 atoms of the heteroalkylene group connecting to the 3 to 10 atoms of the main chain are each independently a carbon atom or a heteroatom, wherein each heteroatom is independently O, S, S(O), S(O)2, Si(R)2, or S(O)2. C )2、Ge(R C 2. P(R) P ) or N(R N ), where each R C Independently selected from the following groups: (C1-C40) hydrocarbon groups, each R P It is (C1-C) 40 ) hydrocarbon group; and each R N It is (C1-C) 40 The hydrocarbon group may or may not exist; and R 1-16 Each person independently chooses from the following groups: (C1-C 40 ) hydrocarbon group, (C1-C 40 ) heterohydrocarbon group, Si(R) C 3. Ge(R) C 3. P(R) P )2、N(R N 2. OR C SR C NO2, CN, CF3, R C S(O)-、R C S(O)2-、(R C )2C=N-、R C C(O)O-、R C OC(O)-, R C C(O)N(R)-、(R C )2NC(O)-, halogen atoms, hydrogen atoms and any combination thereof.

[0043] In another embodiment, R 1 To R 16 At least one of the positions can be substituted by a Si(Y1)(Y2)(Y3) group; Y1 is (C3-C40 ) hydrocarbon group or (C2-C 40 ) heterohydrocarbon group; Y2 is (C1-C 40 ) hydrocarbon group or (C1-C 40 ) heterohydrocarbon group; Y3 is (C1-C 40 ) hydrocarbon group or (C1-C 40 ( ) Heteroalkyl groups, further condition being that Y1, Y2, and Y3 are not all isopropyl; and hydrocarbon groups, heteroalkyl groups, Si(R C 3. Ge(R) C 3. P(R) P )2、N(R N 2. OR C SR C R C S(O)-、R C S(O)2-、(R C )2C=N-、R C C(O)O-、R C OC(O)-, R C C(O)N(R)-、(R C Each of the 2NC(O)-, alkylene group, and heteroalkylene group is independently unaffected or mediated by one or more R groups. S Substituent substitution, each R S Independently, it is a halogen atom, polyfluorinated, perfluorinated, or unsubstituted (C1-C) 18 Alkyl, F3C-, FCH2O-, F2HCO-, F3CO-, R3Si-, R3Ge-, RO-, RS-, RS(O)-, RS(O)2-, R2P-, R2N-, R 2 C=N-, NC-, RC(O)O-, ROC(O-), RC(O)N(R-) or R2NC(O-), or R S The two together form unsubstituted (C1-C) 18 ) hydrocarbon groups, wherein each R is independently unsubstituted (C1-C2) 18 ) hydrocarbon group.

[0044] In a hybrid catalyst system, the BPP catalyst can contain the same or a different cocatalyst as the CGC. Suitable BPP cocatalysts can be selected from the list of cocatalysts provided above.

[0045] Further details and examples of BPP catalysts are provided in U.S. Publication Nos. 2015 / 0344602, 2015 / 0337063, and 2015 / 0337062, and U.S. Patent No. 9,000,108, all of which are incorporated herein by reference in their entirety.

[0046] thermoplastic olefins

[0047] As described above, this multimodal elastomer is incorporated as an impact modifier into thermoplastic olefins (TPO). According to this disclosure, TPO includes multimodal elastomers, polypropylene, and optional additional embodiments, such as additional elastomers, block compounds, fillers, or combinations thereof.

[0048] Various amounts of multimodal elastomer within the TPO are envisioned. In one or more embodiments, the TPO may comprise 10 wt% to 40 wt%, or 15 wt% to 30 wt% of multimodal elastomer, or 16 wt% to 27 wt%, or 18 wt% to 25 wt% based on the total weight of the TPO composition.

[0049] polypropylene

[0050] TPO polypropylene is a matrix polymer toughened by blending with multimodal elastomer compositions. Various polypropylene compositions are considered suitable. The polypropylene polymer base may contain isotactic homopolymer polypropylene and / or other forms of polypropylene (e.g., syndiotactic or atactic). Based on the total weight of the atactic copolymer polypropylene, the propylene polymer base may contain atactic copolymer polypropylene having an ethylene content of 0.5 wt% to 5.0 wt%. Based on the total weight of the propylene polymer base, the propylene polymer base may contain 95 wt% to 100 wt% atactic copolymer polypropylene. The polypropylene polymer base may contain impact copolymers comprising a rubber phase dispersed in propylene. The molecular weight of the polypropylene used, and therefore its melt flow rate, may vary depending on the application. Discussions of various polypropylene polymers are included, for example, in *Modern Plastics Encyclopedia / 89*, published in mid-October 1988, Volume 65, Issue 11, pp. 86-92.

[0051] Propylene polymer base materials may contain clarifying agents and / or nucleating agents. For example, clarifying agents and / or nucleating agents can alter the way polypropylene chains crystallize and aggregate in the molten state. These agents can increase the onset of crystallization temperature. Clarifying agents (or clarifying agents) are typically organic, non-polymeric molecules. Clarifying agents can often also act as nucleating agents, but nucleating agents are not necessarily clarifying agents. An exemplary clarifying agent may contain a chemical derivative of dibenzyl sorbitol and have a melting temperature within the processing window of the polypropylene resin. Nucleating agents are typically inorganic materials with small average particle size and high melting point. When the nucleating resin is melted in an extruder, the nucleating agent can typically remain solid and provide locations around which polypropylene spherulites can form. An exemplary nucleating agent is a chemical derivative of benzoic acid. For example, nucleating agents can be sodium benzoate, kaolin, and / or talc.

[0052] Specific TPO embodiments may include a multimodal elastomer blended with polypropylene and a block composite compatibilizer as detailed below. In such embodiments, the polypropylene may be in the isotactic form of homopolymer polypropylene, although other forms of polypropylene (e.g., syndiotactic or atactic) may also be used. However, impact copolymers of polypropylene (e.g., those copolymers in which a second copolymerization step of reacting ethylene with propylene is employed) and atactic copolymers (also reactor-modified and typically containing ethylene copolymerized with propylene) may also be used in the TPO formulations disclosed herein. A complete discussion of various polypropylene polymers is contained in the Modern Plastics Encyclopedia / 89, published in mid-October 1988, Volume 65, Issue 11, pp. 86-92, the entire disclosure of which is incorporated herein by reference.

[0053] The molecular weight and thus the melt flow rate of the polypropylene used in this disclosure vary depending on the application. The melt flow rate (MFR) of the polypropylene used herein is typically from about 0.1 g / 10 min to about 200 g / 10 min, preferably from about 0.5 g / 10 min to about 150 g / 10 min, and particularly from about 4 g / 10 min to about 100 g / 10 min when measured at 230 °C and a 2.16 kg load, according to ASTM D1238. As mentioned above, the propylene polymer can be a polypropylene homopolymer, or it can be a random copolymer or even an impact copolymer (which already contains a rubber phase). Examples of impact copolymers include Pro-fax SD242 from LyondellBasell Industries or YUPLENE BX3900 from SK Global Chemical. Examples of suitable homopolymers include H734-52RNA from Braskem or Adstif HA801U from LyondellBasell Industries. Examples of random copolymers include 6D43 from Braskem, and suitable random propylene-ethylene plasmonomers and elastomers may include VISTAMAXX. TM (Manufactured by ExxonMobil) and VERSIFY from The Dow Chemical Co., Midland, MI. TM .

[0054] Various amounts of polypropylene are envisioned in TPO. For example, TPO may contain 30 wt% to 85 wt%, or 40 wt% to 85 wt%, or 50 wt% to 85 wt%, or 50 wt% to 80 wt%.

[0055] Block complex compatibilizer

[0056] In the manufacture of TPO, block complexes or block complex compatibilizers are used to combine multimodal elastomers, polypropylene, and other optional components (e.g., additional elastomers). Block complexes can enhance the dispersion of multimodal elastomers in a polypropylene matrix.

[0057] The term "block copolymer" or "segment copolymer" refers to a polymer comprising two or more chemically distinct regions or segments (referred to as "blocks") linked in a linear manner; that is, a polymer comprising chemically differentiated units that are end-to-end linked (covalently bonded) with respect to polymeric functionality rather than linked in a dangling or grafted manner. In one embodiment, the blocks differ in the following: the amount or type of comonomer incorporated therein, density, amount of crystallinity, type of crystallinity (e.g., polyethylene to polypropylene), crystallite size of the polymer attributable to such a composition, type or degree of stereoregularity (isosteryl or syndiotactic), regional regularity or regional irregularity, amount of branching, including long-chain branching or hyperbranching, homogeneity, or any other chemical or physical property. The block copolymers of this disclosure are characterized by a unique distribution of both polymer polydispersity (PDI or Mw / Mn) and block length distribution, which, in a preferred embodiment, is due to the effect of a combination of one or more shuttle agents and one or more catalysts.

[0058] The term "block complex" refers to polymers including soft copolymers, hard copolymers, and block copolymers having both soft and hard segments, such as diblock polymers, wherein the hard segments of the block copolymer are substantially identical to the composition of the hard copolymer in the block complex, and the soft segments of the block copolymer are substantially identical to the composition of the soft copolymer in the block complex. Block copolymers can be linear or branched.

[0059] "Hard" segments refer to highly crystalline blocks of polymeric units, wherein the monomers are present in an amount greater than 90 mol%, and preferably greater than 93 mol%, more preferably greater than 95 mol%, and most preferably greater than 98 mol%. In other words, the comonomer content in the hard segments is most preferably less than 2 mol%, more preferably less than 5 mol%, more preferably less than 7 mol%, and less than 10 mol%. In some embodiments, the hard segments comprise all or substantially all of the monomers (e.g., propylene units).

[0060] On the other hand, "soft" segments refer to amorphous, substantially amorphous or elastic blocks of polymeric units, wherein the content of comonomer is greater than 10 mol% and less than 90 mol%, and preferably greater than 20 mol% and less than 80 mol%, and most preferably greater than 33 mol% and less than 75 mol%.

[0061] Various olefins are envisioned as monomers and additional comonomers for block complexes. In one embodiment, the monomer is propylene and the additional comonomer is ethylene.

[0062] Specifically, when the comonomer is ethylene, it is preferably present in an amount of 10 mol% to 90 mol%, more preferably 20 mol% to 80 mol%, and most preferably 33 mol% to 75 mol%. Preferably, the copolymer comprises 90 mol% to 100 mol% of propylene hard segments. The hard segments can be greater than 90 mol%, preferably greater than 93 mol%, more preferably greater than 95 mol% of propylene, and most preferably greater than 98 mol% of propylene. These hard segments have a corresponding melting point (T0). m The temperature is above 80°C, or above 100°C, or above 115°C, or above 120°C. Additionally, the block composite preferably has a Tg greater than 100°C, preferably greater than 120°C, and more preferably greater than 125°C. m Preferably, the MFR of the block complex is from 0.1 dg / min to 1000 dg / min, more preferably from 0.1 dg / min to 50 dg / min, and even more preferably from 0.1 dg / min to 30 dg / min. Further, the weight-average molecular weight (Mw) of the block complex in this embodiment of the present disclosure is from 10,000 to about 2,500,000, preferably from 35,000 to about 1,000,000, and even more preferably from 50,000 to about 300,000, preferably from 50,000 to about 200,000.

[0063] The block copolymer polymers of the present invention can differ from conventional random copolymers, physical blends of polymers, and block copolymers prepared by sequential monomer addition. Block copolymers can be distinguished from: 1) random copolymers with properties such as higher melting temperature for a given amount of comonomer, block index, and block copolymer index; 2) physical blends with properties such as better tensile strength, improved breaking strength, finer morphology, improved optical properties, and greater impact strength at lower temperatures; and 3) block copolymers prepared by sequential monomer addition in terms of molecular weight distribution, rheology, shear thinning, rheological ratio, and the presence of block polydispersity.

[0064] Block complexes can be defined by the block complex index (BCI). The term BCI is defined herein as equal to the weight percentage of the block copolymer divided by 100% (i.e., weight fraction). The value of the block complex index can range from 0 to 1.0, where 1.0 would equal 100% block copolymer, and zero would be used for materials such as conventional blends or random copolymers. In other words, for insoluble fractions, the BCI is 1.000, and for soluble fractions, the BCI is specified as a value of zero. In one or more embodiments, the BCI can be less than about 0.4 or from about 0.1 to about 0.3. In other embodiments, the BCI is greater than about 0.4 and up to about 1.0. Additionally, the BCI can range from about 0.4 to about 0.7, about 0.5 to about 0.7, or about 0.6 to about 0.9. In some embodiments, the BCI ranges from about 0.3 to about 0.9, about 0.3 to about 0.8, or about 0.3 to about 0.7, about 0.3 to about 0.6, about 0.3 to about 0.5, or about 0.3 to about 0.4, or about 0.4 to about 0.5. In other embodiments, the BCI ranges from about 0.4 to about 1.0, about 0.5 to about 1.0, or about 0.6 to about 1.0, about 0.7 to about 1.0, about 0.8 to about 1.0, or about 0.9 to about 1.0.

[0065] Specifically, the BCI is based on the indication that the insoluble fraction contains a considerable amount of ethylene, which would not be present if the polymer were merely a blend of iPP homopolymer (i.e., hard segments) and ethylene-propylene (EP) copolymer (i.e., soft segments). To account for this "extra ethylene," a mass balance calculation can be performed to estimate the block composite index based on the amounts of xylene insoluble and soluble fractions and the weight percentage of ethylene present in each fraction.

[0066] According to Equation 1, summing the ethylene weight percentage for each fraction yields the total ethylene weight percentage (in the polymer). This mass balance equation can also be used to quantify the amount of each component in a binary blend, or extended to ternary or n-component blends.

[0067]

[0068] Equation 1

[0069] Apply Equations 2 through 4 to calculate the amount of the soft block (providing an additional source of ethylene) present in the insoluble fraction. By substituting the weight % of the insoluble fraction, C2, into the left-hand side of Equation 2, the weight % of the iPP hard segment and the weight % of the EP soft segment can be calculated using Equations 3 and 4. Note that the weight % of ethylene in the soft EP is set to equal to the weight % of ethylene in the xylene soluble fraction. The weight % of ethylene in the iPP block is set to zero, or, if otherwise known from its DSC melting point or other composition measurements, the value can be placed in its place.

[0070]

[0071] Equation 2

[0072]

[0073] Equation 3

[0074]

[0075] Equation 4

[0076] After taking into account the "extra" ethylene present in the insoluble fraction, the only way for the EP copolymer to exist in the insoluble fraction is for the EP polymer chain to be attached to the iPP polymer block (otherwise it would be extracted into the xylene-soluble fraction). Therefore, when the iPP block crystallizes, it can reduce the likelihood of EP block dissolution and / or prevent EP block dissolution.

[0077] To estimate the BCI, the relative amount of each block must be considered. For a rough estimate of this relative amount, the ratio between soft EP and hard iPP is used. The ratio of the soft EP polymer to the hard iPP polymer can be calculated using Equation 2, from the mass balance of the total ethylene measured in the polymer. Alternatively, it can also be estimated from the mass balance of the monomers and comonomers consumed during polymerization. The weight fractions of hard iPP and soft EP are calculated using Equation 2, assuming that the hard iPP is ethylene-free. The ethylene weight% of soft EP is the amount of ethylene present in the xylene-soluble fraction.

[0078] For example, if the iPP-EP polymer contains a total of 47 wt% C2 and is prepared under conditions for preparing a soft EP polymer with 67 wt% C2 and an iPP homopolymer containing zero ethylene, then the amounts of soft EP and hard iPP are 70 wt% and 30 wt%, respectively. If the percentage of EP is 70 wt% and iPP is 30 wt%, then the relative ratio of EP:iPP blocks can be expressed as 2.33:1. Therefore, if a person skilled in the art performs xylene extraction of the polymer and recovers 40 wt% insoluble fraction and 60 wt% soluble fraction, this will be an unexpected result and will lead to the conclusion that a block copolymer exists. If the ethylene content of the insoluble fraction is subsequently measured to be 25 wt% C2, then equations 2 to 4 can be solved to account for this additional ethylene and it is found that there are 37.3 wt% soft EP polymer and 62.7 wt% hard iPP polymer in the insoluble fraction.

[0079] Depending on the estimation of the total polymer composition and errors in analytical measurements used to estimate the composition of hard and soft blocks, there may be a relative error of 5% to 10% in the calculated block complex index. This estimation includes wt% C2 of the iPP hard blocks as measured by DSC melting point, NMR analysis, or process conditions; or the average wt% C2 of the soft blocks as estimated from the xylene-soluble composition, or by NMR, or by the DSC melting point of the soft blocks (if detected). However, overall, the block complex index calculation reasonably accounts for the unexpected amount of “extra” ethylene present in the insoluble fraction, the only way for the EP copolymer to be present in the insoluble fraction is that the EP polymer chain must be attached to the iPP polymer block (otherwise it would be extracted into the xylene-soluble fraction).

[0080] Block complexes and crystalline block complex polymers are preferably prepared by a method comprising contacting an addition-polymerizable monomer or mixture of monomers with a composition comprising at least one addition polymerization catalyst, a co-catalyst, and a chain shuttle under addition polymerization conditions. The method is characterized by forming at least some of the grown polymer chains in two or more reactors operating under steady-state polymerization conditions or in two or more zones or reactors operating under plug flow polymerization conditions, under different method conditions. In specific embodiments, the block complexes of this disclosure comprise block polymer fractions having the most probable block length distribution.

[0081] Suitable methods for producing block complexes and crystalline block complexes can be found, for example, in U.S. Publication No. 2008 / 0269412, published October 30, 2008, which is incorporated herein by reference in its entirety. Specifically, the polymerization is preferably carried out as a continuous polymerization, preferably a continuous solution polymerization, wherein the catalyst component, monomers, and optionally solvents, auxiliaries, scavengers, and polymerization aids are continuously supplied to one or more reactors or zones, and the polymer product is continuously removed therefrom. Within the scope of the term "continuous" as used in this context are those methods in which reactants are added intermittently and products are removed at small regular or irregular intervals so that the overall method is substantially continuous over time. Furthermore, as previously mentioned, one or more chain shuttle agents may be added during polymerization, including in the first reactor or zone, upon exiting the first reactor or slightly before exiting the first reactor, or at any point between the first reactor or zone and a second or any subsequent reactor or zone. Due to differences in monomers, temperature, pressure, or other polymerization conditions between at least two reactors or zones connected in series, polymer segments with different compositions within the same molecule, such as comonomer content, crystallinity, density, stereoregularity, regioregularity, or other chemical or physical differences, are formed in different reactors or zones. The size of each segment or block is determined by the continuous polymer reaction conditions and preferably by the most probable distribution of polymer size.

[0082] When block complexes are produced using a continuous process, their PDI can be 1.7 to 15, or 1.8 to 3.5, or 1.8 to 2.2, or 1.8 to 2.1. When produced using a batch or semi-batch process, the PDI can be 1.0 to 2.9, or 1.3 to 2.5, or 1.4 to 2.0, or 1.4 to 1.8. Such block complexes are described, for example, in U.S. Publications 2011 / 0082257, 2011 / 0082258, and 2011 / 0082249, and descriptions of the block complexes, procedures for their preparation, and methods for their analysis are all incorporated herein by reference.

[0083] In one embodiment, the block complex is present in an amount of 2 wt% to 15 wt%, preferably 2 wt% to 10 wt%, and more preferably 2 wt% to 5 wt%, based on the total weight of TPO.

[0084] Additives and fillers

[0085] Optional additives, such as antioxidants (e.g., hindered phenols, e.g., Irganox) TM 1010), phosphites (e.g., Irgafos) TM168), adhesive additives (e.g., PIB), anti-blocking additives, pigments, fillers (e.g., talc, diatomaceous earth, nanofillers, clay, metal particles, glass fibers or particles, carbon black, other reinforcing fibers, etc.) may also be included in the formulation. Preferably, the composition comprises 0 wt% to 30 wt%, or 0 wt% to 20 wt%, or 5 wt% to 20 wt% of talc based on the total weight of TPO. In some embodiments, the desired TPO is produced without talc. Other additives may be present in amounts from 0.01 wt% to 1 wt%.

[0086] General product manufacturing

[0087] The TPO compositions disclosed herein can be produced into parts, sheets, or other articles using any conventional extrusion, calendering, blow molding (e.g., as described in *Modern Plastics Encyclopedia / 89*, mid-October 1988, Vol. 65, No. 11, pp. 217-218, “Extrusion-Blow Molding,” the disclosure of which is incorporated herein by reference), injection molding (e.g., as described in *Modern Plastics Encyclopedia / 89*, mid-October 1988, Vol. 65, No. 11, pp. 264-268, “Introduction to Injection Molding” and pp. 270-271, “Injection Molding Thermoplastics,” the disclosure of which is incorporated herein by reference), foaming, or thermoforming methods. Specific examples of such methods include sheet extrusion, profile extrusion, and injection molding. This method can produce articles or products with smooth or embossed surfaces. The components of the composition can be premixed and fed into the method, or the components can be fed directly into the method equipment, such as a conversion extruder, so that the composition is formed during extrusion, calendering, blow molding, foaming, or thermoforming. The composition can also be blended with another polymer before manufacturing the article. This blending can be carried out by any of a variety of conventional techniques, one of which is the dry blending of pellets of the thermoplastic elastomer composition invented for this invention with pellets of another polymer.

[0088] A partial, and far-exhaustive, list of articles that can be manufactured using the compositions of the present invention includes automotive body parts such as dashboards, dashboard foams, fuel tanks, automotive containers, bumper panels, body side moldings, automotive structural ribs, interior pillars, exterior trim, interior trim, air dams, air ducts, grilles, and wheel covers, as well as non-automotive applications such as polymer films, polymer sheets, foams, tubing, fibers, coatings, trash cans, and storage or packaging containers, including, for example, freezer containers. Of course, those skilled in the art can also combine polymers to advantageously utilize refractive indices to improve or maintain the transparency of end-use articles, such as freezer containers.

[0089] Additional articles include lawn furniture, lawnmower and other gardening equipment parts, refrigerator and other household appliance parts, recreational vehicle parts, golf cart parts, utility vehicle parts, tabletop edging, toy and watercraft parts. The composition can also be used in roofing applications, such as roofing products. The composition can be further used in building applications, such as in plastic-timber, trim, siding, dashboards, vaults, and other interior and exterior building trim. The composition can be further used in the manufacture of footwear components. The composition can be further used in the manufacture of components for handheld electronic devices, such as cellular phones, personal digital players, personal digital assistants, etc. Technicians can easily expand this list without extensive experimentation. Additional articles include extruded profiles.

[0090] Example

[0091] The following examples illustrate one or more additional features of this disclosure described above. Table 1 below provides the materials used in the preparation of the following multimodal elastomers, block composites, and thermoplastic olefins. Furthermore, Table 1 lists and studies comparative unimodal elastomers.

[0092] Table 1: Materials

[0093]

[0094] Preparation of multimodal elastomers

[0095] Multimodal elastomers were prepared using either dual-reactor or single-reactor systems. These reactors were hydraulically filled and operated under steady-state conditions. The catalysts and co-catalysts used to produce the multimodal elastomers are listed in Table 2, as described below. The inventive multimodal elastomers were prepared using a combination of a first catalyst comprising a biphenol complex and a second catalyst comprising a complex with a defined geometry. Comparative multimodal elastomer (Comparative C) was prepared in a single reactor using a combination of two biphenol complex catalysts. For single-reactor multimodal elastomers, ethylene and octene monomers, solvent, hydrogen, catalyst, and co-catalyst were fed into the reactor according to the process conditions outlined in Tables 3 and 4 to produce the multimodal elastomers. Multimodal examples 1 to 4 and comparative multimodal examples (Comparative A, Comparative B, and Comparative C) were prepared in a continuous stirred tank reactor. Multimodal examples 5 to 9 were produced in a loop reactor.

[0096] In addition to the single-reactor multimodal elastomers detailed above, Table 5 provides processing conditions for preparing multimodal elastomers using two reactors connected in parallel. Here, each reactor is hydraulically filled and operated under steady-state conditions. Based on the process conditions outlined in Table 5, ethylene and octene monomers, solvent (ISOPAR) are used... ® E), hydrogen, BPP-B catalyst, co-catalyst-1, and co-catalyst-2 are fed into the first reactor (loop reactor). Additional ethylene and octene monomers, solvent, hydrogen, CGC-A catalyst, co-catalyst-2, and co-catalyst-3 are added to the second reactor (continuous stirred tank reactor) according to the process conditions outlined in Table 5. The contents of the two reactors are combined, and the solvent is then removed to produce the multimodal elastomer.

[0097] Table 6 describes the properties of multimodal elastomers.

[0098] Table 2: Catalysts and co-catalysts used to produce multimodal elastomers

[0099]

[0100]

[0101] Table 3: Process Conditions for Multimodal Elastomers in Dual Catalysts and Single Reactors - Part 1

[0102]

[0103] Table 4: Process Conditions for Multimodal Elastomers in Dual Catalysts and Single Reactors - Part 2

[0104]

[0105] Table 5: Process conditions for multi-peak elastomers used in dual-catalyst, dual-reactor systems

[0106]

[0107] Table 6. Physical properties of multimodal (dual catalyst / single reactor and dual catalyst / dual reactor) and unimodal elastomers

[0108]

[0109]

[0110] --Unmeasured

[0111] *HMW C8 wt% - LMW C8 wt%

[0112] refer to Figure 1 Examples of dual-catalyst, single-reactor multi-peak elastomers (Example 5) and dual-catalyst, dual-reactor multi-peak elastomers (Example 10) are shown, along with ENGAGE. TM 8100, GPC data for a comparative example of a unimodal elastomer. As shown in the figure, regardless of whether the multimodal elastomer is produced in a single-reactor system or a two-reactor system, the multimodal elastomer exhibits a wider molecular weight distribution and a higher molecular weight than the unimodal elastomer. Referring to Table 6, all examples have an HMW fraction, where Mn is greater than that of the unimodal elastomer. TM Example. For applications in TPO compounds, high molecular weight elastomers are required for impact toughening properties; however, the high molecular weight must be balanced with the total viscosity of the elastomer to ensure that the elastomer is dispersed in the PP matrix and that the overall low viscosity of the TPO compound is suitable for injection molding processability. Figure 2 The figure shows DMS rheological data for the same elastomer. As shown in the figure, multi-peak examples 5 and 10 and the uni-peak elastomer ENGAGE are also presented. TM 8100 exhibits a very similar shear viscosity. Therefore, multimodal elastomers can have higher molecular weights, which is ideal for impact toughening in TPO; however, they maintain a high shear viscosity (V100) comparable to unimodal elastomers, which is ideal for processability. The high shear viscosity better describes the rheological properties of the elastomer in a twin-screw extruder or under typical mixing conditions in injection molding.

[0113] In some cases, the combination of CGC and BPP catalysts in a single reactor does not allow for low viscosity and high Mw HMW fractions. For example, Comparative A and Comparative B only have 5 wt% to 6 wt% LMW fractions. The V100 of the elastomer is greater than 2000 Pa·s, higher than any of the inventive examples, but the HMW Mn values ​​are only 67 kg / mol and 61 kg / mol, significantly lower than the inventive examples.

[0114] Additionally, as shown in Table 6, the comparative C, which incorporates two BPP catalysts, produces an LMW fraction with less than 29 wt% octene incorporation, particularly 25 wt%. As shown in the table below, when multimodal elastomers are incorporated into TPO, less than 29 wt% α-olefins and more than 71 wt% ethylene are detrimental.

[0115] Preparation of block complex compatibilizers (BC1, BC2 and BC3)

[0116] The block composite compatibilizers incorporated into the TPO compounds described below are designated BC1, BC2, and BC3. They are prepared using two reactors connected in series. Each reactor is hydraulically filled and configured to operate under steady-state conditions. Propylene and ethylene monomers, solvent, hydrogen, BPP-B, co-catalyst-1, co-catalyst-2, and CSA-1 are fed into the first reactor according to the process conditions outlined in Table 7. The contents of the first reactor are then fed into the second reactor in series, as described in Table 7. Additional monomers, solvent, hydrogen, BPP-B, co-catalyst-1, and optionally co-catalyst-2 are added to the second reactor.

[0117] Table 8 summarizes the properties of the block complex, and Table 9 describes the block complex index values.

[0118] Table 7 - Polymer processes for block composites

[0119]

[0120] Table 8 - Physical properties of the block complex

[0121]

[0122] Table 9 - Block Complex Index

[0123]

[0124] TPO blend

[0125] TPO compounds were prepared on a Coperion ZSK-25 mm twin-screw extruder equipped with a water bath and wire cutter. The compounding conditions are listed in Table 12 below. All components were added through the main feed throat. The polymer components of the TPO formulations listed in Tables 10 and 11 were dry-blended with Irganox® B225 antioxidant and fed through a loss-in-weight feeder. A few drops of oil were added to the pellets to help adhere the antioxidant powder to the pellets. For TPO formulations containing talc listed in Table 11 below, the talc was fed into the main feed throat through a separate powder feeder.

[0126] Table 10: Talc-Free TPO Formulations

[0127]

[0128] Table 11: Talc-filled TPO formulations

[0129]

[0130] Table 12: Blending Conditions

[0131]

[0132] ASTM D638 Type I stretch bars, ISO A stretch bars, and flow spirals are injection molded. Table 13 shows typical molding conditions used on a Krauss-Maffei KM 110-390 / 390 CL injection molding machine equipped with an Axxicon mold base. The channel dimensions of the spiral flow mold are 2 mm × 5 mm × 1150 mm. Record the flow length after molding according to the conditions listed in Table 13.

[0133] Table 13: Injection Molding Conditions

[0134]

[0135] Table 14: Properties of TPO for use in talc-free TPO compounds

[0136]

[0137] Table 15: TPO Properties of TPO Compounds Used for Filling

[0138]

[0139] The properties of TPO are shown in Tables 14 and 15. Referring to Table 14, the unfilled (talc-free) TPO compounds TPO 1 and TPO 2, which contain multi-peak elastomer examples 5 (single reactor) and 10 (dual reactor), respectively, exhibited higher injection flow than TPO Comparison A, which contains the ENGAGE single-peak elastomer. Furthermore, TPO 1 and TPO 2 exhibited improved notched impact toughness compared to TPO Comparison A. Specifically, Charpy strength was significantly improved at temperatures of 0°C and 23°C. In addition, TPO 1 and TPO 2 also provided much higher tensile elongation at break than TPO Comparison A, especially for the single-reactor multi-peak elastomer TPO 1.

[0140] Referring to Table 15, which shows that TPO compounds with talc filler, combined with improved or comparable injection flow, achieve better low-temperature notched impact toughness. Specifically, TPO 3 and TPO 4 exhibit significantly greater Izod strength at -40°C than TPO control B, which contains ENGAGE. TM8842 unimodal elastomer. TPO 3, containing 10 wt% talc, exhibits at least 4 times higher Izod strength than TPO Comparison B at -40°C. With 20 wt% talc, TPO 5, containing ENGAGE unimodal elastomer, exhibits at least 3 times higher Izod strength than TPO Comparison C and TPO Comparison D at -40°C. TPO 5 also has higher injection flow than TPO Comparison C and TPO Comparison D. Compared to TPO Comparison E, at a relatively slightly lower injection flow, TPO 5 exhibits significantly improved Izod impact strength, at least 10 times higher than TPO Comparison E at -40°C.

[0141] Referring again to Table 15, and comparing with the single-peaked control ENGAGE TM Compared to 8842, a multimodal elastomer TPO Comparison G, made from two biphenol catalysts, did not show improved impact resistance in the talc-filled formulation TPO Comparison F.

[0142] Measurement Standards

[0143] Melt index or I2: Measured using ASTM D 1238, conditions 190°C, 2.16 kg.

[0144] Melt flow rate or MFR: Measured using ASTM D 1238, conditions 230°C, 2.16 kg.

[0145] Mooney viscosity: Measured at 125°C using ML1 + 4 conditions according to ASTM D1646.

[0146] Density: Measured according to ASTM D792.

[0147] Dynamic mechanical spectroscopy (DMS) - Rheology: Rheology of the samples was analyzed by DMS using an Advanced Rheometric Expansion System (ARES) equipped with a 25 mm stainless steel parallel plate. Isothermal dynamic frequency sweeps were performed in the frequency range of 0.1 rad / s to 100 rad / s under nitrogen purging at 190 °C. Samples with a diameter of approximately 25.4 mm were cut from a compression-molded plate. The sample was placed on the lower plate and allowed to melt for 5 minutes. The plate was then closed to a 2.0 mm gap, and the sample was trimmed to a diameter of 25 mm. The sample was equilibrated at 190 °C for 5 minutes before starting the test. Complex viscosity was measured at a constant strain amplitude of 10%. Viscosities at 0.1 rad / s (V0.1) and 100 rad / s (V100) are reported.

[0148] High-temperature gel permeation chromatography (HT GPC):

[0149] Molecular weight (MW) and molecular weight distribution (MWD) were determined using a high-temperature gel permeation chromatography (GPC IR) system consisting of an infrared concentration detector (IR-5) from PolymerChar Inc (Valencia, Spain). The carrier solvent was 1,2,4-trichlorobenzene (TCB). The autosampler chamber was operated at 160 °C, and the column chamber at 150 °C. Four Polymer Laboratories Mixed A LS 20 μm columns were used. The chromatographic solvent (TCB) and sample preparation solvent were from the same solvent source, containing 250 ppm butylated hydroxytoluene (BHT) and nitrogen injection. The sample was prepared in TCB at a concentration of 2 mg / mL. The polyethylene sample was gently shaken at 160 °C for 2 hours. The injection volume was 200 µl, and the flow rate was 1.0 mL / min.

[0150] The GPC column array was calibrated using 21 narrow molecular weight distribution polystyrene standards. The standards ranged in molecular weight from 580 g / mol to 8,400,000 g / mol and were arranged in six “cocktail” mixtures, with individual molecular weights differing by at least a decimal place.

[0151] The maximum molecular weight of polystyrene standards was converted to the molecular weight of polyethylene using the following equation (as described by Williams and Ward, *Journal of Polymer Science*, *Polym. Let.*, 6, 621 (1968)):

[0152] (1)

[0153] Here, the value of B is 1.0, and the experimentally determined value of A is approximately 0.42.

[0154] The corresponding polyethylene equivalent calibration point obtained from equation (1) is fitted to the elution volume of the observed polystyrene standard using a third-order polynomial.

[0155] Calculate the number-average molecular weight, weight-average molecular weight, and z-average molecular weight using the following equations:

[0156] (2) (3)

[0157] (4)

[0158] Among them, Wf i It is the weight fraction of the i-th component, and M iIt is the molecular weight of the i-th component.

[0159] MWD is expressed as the ratio of weight-average molecular weight (Mw) to number-average molecular weight (Mn).

[0160] The accurate value of A is determined by adjusting the value of A in equation (1) until Mw and the corresponding retention volume polynomial are calculated using equation (3), which are consistent with the known value of Mw of 120,000 g / mol for the standard linear polyethylene homopolymer reference.

[0161] GPC deconvolution:

[0162] Deconvolution is performed on GPC data to yield the most probable fits for two molecular weight components. Numerous deconvolution algorithms are available both commercially and in the literature. These can lead to different results depending on the assumptions used. The algorithm summarized here is optimized for deconvolution of the two most probable molecular weight distributions (plus an adjustable error term). To allow for variations in the fundamental distribution due to small fluctuations in macromonomer incorporation and reactor conditions (i.e., temperature, concentration), the basis function is modified to include a normal distribution term. This terminology allows the basis function for each component to be "smeared" to varying degrees along the molecular weight axis. The advantage is that, in the limiting conditions (low LCB, perfect concentration, and temperature control), the basis function becomes a simple, most probable Flory distribution.

[0163] Three components (j = 1, 2, 3) are derived, where the third component (j = 3) is an adjustable error term. The GPC data must be normalized and appropriately converted to a weight fraction logarithm. 10 Molecular weight vector. In other words, each potential curve used for deconvolution should be represented by a height vector h. i Composed of, with Log 10 The known intervals for molecular weight reporting height, h i It has been appropriately transformed from the elution volume domain to Log. 10 Molecular weight domain, and h i Normalized. Additionally, this data should be available for use by Microsoft Excel™ applications.

[0164] Several assumptions were made during deconvolution. Each component j consists of the most probable Flory distribution, which has been used with parameters... j Convolve with a normal or Gaussian spread function. The resulting three basis functions are used for chi-square X. 2 During the minimization process, the best fit h is located. i The parameters of the n points and the GPC data vector.

[0165]

[0166] Use the Excel™ function "NORMDIST(x, average, standard_dev, cumulative)" to calculate the variable CumND. j,k The parameter settings are as follows:

[0167]

[0168] Accumulation = True

[0169] Table 16 below summarizes these variables and their definitions. The Excel™ software application Solver is sufficient for this task. Constraints are added to Solver to ensure proper minimization.

[0170] Table 16: Variable Definitions

[0171]

[0172] The eight parameters derived from chi-square minimization are μ1, μ2, μ3, 1. 2. 3. w1 and w2. Then, term w3 is derived from w1 and w2 because the sum of the three components must equal 1. Table II is a summary of the Solver restrictions used in the Excel program.

[0173] Table 17: Summary of Limitations

[0174]

[0175] The additional restricted inclusion constraint to be understood is only μ. j > 0 is allowed, but this constraint does not need to be entered if the solver is correctly initialized, because the solver routine will not move any μ. j Values ​​less than approximately 0.005. Furthermore, w j All are interpreted as positive. This constraint can be handled outside the solver. If w j This is understood as generating the value by selecting two points along the interval 0.0 < P1 < P2 < 1.0; where w1 = P1, w2 = P2 - P1 and w3 = 1.0 – P2; then constrained P1 and P2 are equal to the values ​​of w1 and P2 above. j The required restrictions.

[0176] Table 18 is a summary of the solver settings under the Options tab.

[0177] Table 18: Solver Settings

[0178]

[0179] The values ​​μ1, μ2, w1, and w2 can be obtained by assuming two ideal Flory components for the observed weight-average molecular weight, number-average molecular weight, and z-average molecular weight of the observed GPC distribution.

[0180]

[0181] Then calculate the values ​​of μ1, μ2, w1, and w2. These should be carefully tuned before proceeding to the solver in the minimization step to allow for a small error term w3 and to satisfy the constraints in Table II. j The initial value is set to 0.05.

[0182] Octene content was determined from HT GPC IR:

[0183] Octene content was determined using an IR-5 composition detector from Polymer Carbon. IR fixed-band signals for “methyl,” “methylene,” and “measured” (“methyl” + “methylene”) were collected and processed for IR-5 composition mode. The composition detector was calibrated using ethylene / octene (EO) copolymers produced from 11 metallocene solutions, containing 0 wt% to 40 wt% octene, and a polyoctene (PO) homopolymer (100 wt% octene). The Mw values ​​for all polymers were approximately 40 K or 100 K. Signals at peak positions were used for calibration. These EO copolymers and PO polymers established a linear relationship between octene wt% and the IR-5 “methyl” / “measured” signal ratio.

[0184] The octene wt% distribution of the resin was obtained by linear calibration using the IR-5 “methyl” / “measured” signal and the octene wt% and IR-5 “methyl” / “measured” signal ratio. The polymer chain end effect was corrected for one vinyl and one methyl group at the end of each chain.

[0185] For bimodal resins, the wt% of octene in each fraction is calculated as follows. For high weight fractions (main peak), the wt% of octene is calculated using the plateau of the distribution curve at the main peak region. For low weight fraction regions (small peaks), the wt% of octene is calculated within a narrow MW range (0.3 of the log MW scale) to avoid contamination of the main peak, and the scattering of the wt% octene signal ends at low elution concentrations.

[0186] Flexural modulus: After conditioning at 73℉ and 50% relative humidity for at least 40 hours, the flexural modulus is tested according to ISO 178 at 2 mm / min or ASTM D790 at 0.05 inch / min. The 1% secant modulus is reported as the average of at least five specimens. Specimens are taken from injection-molded ISO A or ASTM D638 Type I tensile test strips.

[0187] Izod Impact Strength: The notched Izod impact test was performed on injection-molded ASTM specimens cut from ASTM D638, Type 1 tensile test strips, with dimensions of 62 mm × 19 mm × 3.175 mm. The specimens were notched using a notching machine to produce a notch depth of 10.16 ± 0.05 mm according to ASTM D256. Five specimens of each sample were tested at test temperatures of 23°C, 0°C, and -40°C using ASTM D256. The energy values ​​in kJ / m³ are reported. 2 .

[0188] Charpy Impact Strength: The notched Charpy impact test was performed on injection-molded ISO specimens cut from ISO A tensile test strips. The specimens were notched using a notching machine according to ISO 179. Ten specimens of each sample were tested at test temperatures of 23°C, 0°C, and -30°C using ISO 179. The energy values ​​(kJ / m³) are reported. 2 .

[0189] Tensile properties are measured according to ASTM D638 using injection-molded ASTM D638, Type 1 tensile test bar and a crosshead speed of 2 inches per minute, or according to ISO 527 using injection-molded ISO A tensile test bar and a crosshead speed of 50 mm / minute.

[0190] Differential scanning calorimetry (DSC) is used to measure the crystallinity of polymers, such as ethylene-based (PE) polymers. Approximately 5 to 8 mg of polymer sample is weighed and placed in a DSC pan. The lid is screwed onto the pan to ensure a sealed atmosphere. The sample pan is placed in the DSC unit and then heated at a rate of approximately 10 °C / min to a temperature of 180 °C for PE (230 °C for polypropylene or "PP"). The sample is held at this temperature for three minutes. The sample is then cooled at a rate of 10 °C / min to -60 °C for PE (-40 °C for PP) and held isothermally at said temperature for three minutes. The sample is then heated at a rate of 10 °C / min until completely melted (second heating). The heat of melting (H2) is determined by the second heating curve. f Divide the theoretical heat of fusion for PE by 292 J / g (for PP, 165 J / g) and multiply this by 100 to calculate the crystallinity percentage (e.g., crystallinity % = (H) f / 292 J / g) x 100 (for PE)).

[0191] Unless otherwise stated, each polymer's One or more melting points (T) m ) It is determined by the second heating curve (peak Tm), and Crystallization temperature (T) c )The peak Tc is determined by the first cooling curve. Regarding DSC, the temperature at the maximum heat flow rate relative to the linear baseline is used as the melting point. The linear baseline is constructed from the start of melting (above the glass transition temperature) to the end of the melting peak. For example, the temperature can be increased from room temperature to 200°C at 10°C / min, maintained at 200°C for 5 minutes, decreased to 0°C at 10°C / min, maintained at 0°C for 5 minutes, and then the temperature can be increased from 0°C to 200°C at 10°C / min, and the data can be taken from this second heating cycle.

[0192] High-temperature liquid chromatography (HTLC):The high-temperature liquid chromatography (HTLC) experiment was conducted with minor modifications according to a published method (Lee, D.; Miller, MD; Meunier, DM; Lyons, JW; Bonner, JM; Pell, RJ; Shan, CLP; Huang, T. *Journal of Chromatography*, A 2011, 1218, 7173). Two Shimadzu (Columbia, MD, USA) LC-20AD pumps were used to deliver decane and trichlorobenzene (TCB), respectively. Each pump was connected to a 10:1 fixed separator (part number #: 620-PO20-HS, Analytical Scientific Instruments Inc., CA, USA). According to the manufacturer, the separator had a pressure drop of 1500 psi in H2O at 0.1 mL / min. The flow rate of both pumps was set to 0.115 mL / min. After separation, the secondary flow of decane and TCB was 0.01 mL / min, determined by weighing the collected solvent over 30 minutes. The volume of collected eluent was determined by the mass and density of the solvent at room temperature. The secondary flow was delivered to the HTLC column for separation. The main flow was returned to the solvent reservoir. A 50-µL mixer (Shimadzu) was connected after the separator to mix the solvent from the Shimadzu pump. The mixed solvent was then delivered to a syringe in the oven of a Waters GPCV2000 (Milford, MA, USA). A Hypercarb™ column (2.1 × 100 mm, 5 μm particle size) was connected between the syringe and a 10-port VICI valve (Houston, TX, USA). The valve was equipped with two 60 μL sample loops. The valve was used to continuously feed eluent from the first-size (D1) HTLC column to the second-size (D2) SEC column. A Waters GPCV2000 pump and a PLgel Rapid™-M column (10 × 100 mm, 5 μm particle size) were connected to a VICI valve for D2 size exclusion chromatography (SEC). A symmetrical configuration was used for the connection described in the literature (Brun, Y.; Foster, P. *Journal of Separation Sciences*, 2010, 33, 3501). A dual-angle light scattering detector (PD2040, Agilent Technologies, Santa Clara, CA, USA) and an IR5 infrared absorption detector were connected after the SEC column for the measurement of concentration, composition, and molecular weight.

[0193] Separation for HTLC: Approximately 30 mg was dissolved in 8 mL of decane by gently shaking the vial at 160°C for 2 hours. Decane contained 400 ppm BHT (2,6-di-tert-butyl-4-cresol) as a free radical scavenger. The sample vial was then transferred to the GPCV2000 autosampler for injection. Throughout the separation process, the temperature of the autosampler, syringe, Hypercarb and PLgel columns, 10-port VICI valve, and LS and IR5 detectors were maintained at 140°C.

[0194] The initial conditions prior to injection were as follows: The flow rate for the HTLC column was 0.01 mL / min. The solvent composition in the D1 Hypercarb column was 100% decane. The flow rate for the SEC column was 2.51 mL / min at room temperature. The solvent composition in the D2 PLgel column was 100% TCB. The solvent composition in the D2 SEC column remained constant throughout the separation process.

[0195] Aliquots of 311 μL sample solution were injected into the HTLC column. The injection triggered the gradient described below:

[0196] 0 to 10 minutes, 100% decane / 0% TCB;

[0197] From 10 minutes to 651 minutes, TCB increased linearly from 0% TCB to 80% TCB.

[0198] The injection also triggered the collection of light scattering signals and “measurement” and “methyl” signals from the IR5 detector using the EZChrom™ Chromatography Data System (Agilent) at a 15° angle (LS15). 测量 and IR 甲基 The analog signal from the detector was converted into a digital signal using an SS420X analog-to-digital converter. The collection frequency was 10 Hz. The injection also triggered the opening and closing of the 10-port VICI valve. The valve opening and closing was controlled by a relay signal from the SS420X converter. The valve opened and closed once every 3 minutes. Chromatograms were collected from 0 minutes to 651 minutes. Each chromatogram consisted of 651 / 3 = 217 SEC chromatograms.

[0199] Following gradient separation, 0.2 mL of TCB and 0.3 mL of decane were used to wash and reequilibrate the HTLC column for the next separation. This step was performed at a flow rate of 0.2 mL / min, delivered via a Shimadzu LC-20 AB pump connected to the mixer.

[0200] Data analysis for HTLC: The raw 651-minute chromatogram was first defolded to obtain 217 SEC chromatograms. Each chromatogram was 0 mL to 7.53 mL in 2D elution volumes. Integration limits were then set, and peak removal, baseline calibration, and smoothing were performed on the SEC chromatograms. The method was similar to batch analysis of multiple SEC chromatograms in a conventional SEC process. The sum of all SEC chromatograms was checked to ensure that both the left-hand side (upper limit of integration) and the right-hand side (lower limit of integration) of the peak were at baseline zero. Otherwise, the integration limits were adjusted to repeat the method.

[0201] Each SEC chromatogram n from 1 to 217 yields X to Y pairs in the HTLC chromatogram, where n is the number of fractions:

[0202] X n = Elution volume (mL) = D1 flow rate × n × t 开关

[0203] Where t 开关 = 3 minutes is the opening and closing time of a 10-port VICI valve.

[0204] Y n = Signal strength (voltage) =

[0205] The above equation uses IR 测量 The signal is used as an example. The obtained HTLC chromatogram shows the concentration of the separated polymeric components as a function of elution volume. Normalized IR 测量 HTLC chromatograms are represented by dW / dV, where Y represents the weight fraction normalized relative to the elution volume.

[0206] Also from I R甲基 The X-to-Y pair data is obtained from the LS15 signal. R甲基 / I R测量 The ratio is used to calculate the composition after calibration. After calibration, LS15 / I R测量 The ratio is used to calculate the weight-average molecular weight (WM). Mw ).

[0207] Calibration followed the method described by Lee et al. High-density polyethylene (HDPE), isotactic polypropylene (iPP), and ethylene-propylene copolymers with propylene contents of 20.0 wt%, 28.0 wt%, 50.0 wt%, 86.6 wt%, 92.0 wt%, and 95.8 wt% P were used for IR calibration. 甲基 / IR 测量 Calibrated standards. The composition of the standards was determined by NMR. The standards were run using an SEC with an IR5 detector. The obtained IR values ​​of the standards were plotted.甲基 / IR 测量 The ratio is used as a function of the composition to generate a calibration curve.

[0208] The HDPE reference is used for routine LS15 calibration. The reference's M... w The pre-determined concentration (QC) was 104.2 kg / mol using a GPC with an LS and RI (refractive index) detector. NBS 1475 was used as the standard in the GPC. The standard's detection value was 52.0 kg / mol by NIST. Standards ranging from 7 mg to 10 mg were dissolved in 8 mL of decane at 160°C. The solution was injected into an HTLC column in 100% TCB. The polymer was eluted at a constant 100% TCB at 0.01 mL / min. Therefore, the polymer peak appeared at the vacancy volume of the HTLC column. The calibration constant Ω was determined by the total LS15 signal (A). LS15 ) and total IR 测量 Signal (A IR,测量 )Sure:

[0209]

[0210] Then the experiment LS15 / IR 测量 The ratio is converted to M via Ω. w .

[0211] Xylene soluble fraction analysis: The process was performed by dissolving the xylene in 200 ml of o-xylene under reflux conditions for 2 hours using a weighed resin. The solution was then cooled to 25°C in a temperature-controlled water bath to allow the xylene-insoluble (XI) fraction to crystallize. Once the solution had cooled and the insoluble fraction had precipitated out, separation of the xylene-soluble (XS) fraction from the xylene-insoluble fraction was accomplished by filtration through filter paper. The remaining o-xylene solution was evaporated from the filtrate. Both the XS and XI fractions were dried in a vacuum oven at 100°C for 60 minutes and then weighed.

[0212] 13 12C nuclear magnetic resonance (NMR) The following are involved:

[0213] Sample preparation: The sample was prepared by adding approximately 2.7 g of tetrachloroethane-d2 / o-dichlorobenzene (a 0.025 M 50 / 50 mixture) in chromium acetylacetonate (relaxant) to 0.21 g of sample in a 10 mm NMR tube. The sample was dissolved and homogenized by heating the tube and its contents to 150 °C.

[0214] Data acquisition parameters: Data were collected using a Bruker 400 MHz spectrometer equipped with a Bruker Dual DUL high-temperature CryoProbe. Data were acquired using 320 transient values ​​per data file, a 7.3-second pulse repetition delay (6-second delay + 1.3-second acquisition time), a 90-degree tilt angle, inverse gating decoupling, and a sample temperature of 125°C. All measurements were performed on non-rotating samples in locked mode. Samples were immediately homogenized before insertion into a heated (130°C) NMR transducer and allowed to thermally equilibrate in the probe for 15 minutes prior to data acquisition.

[0215] It will be apparent to those skilled in the art that various modifications can be made to the described embodiments without departing from the spirit and scope of the claimed subject matter. Therefore, this specification is intended to cover modifications and variations of the described embodiments, provided that such modifications and variations are within the scope of the appended claims and their equivalents.

[0216] This disclosure relates to the following implementation plan:

[0217] 1. A multimodal elastomer comprising a copolymer of ethylene and at least one α-olefin monomer, wherein the multimodal elastomer comprises:

[0218] 20% to 90% by weight of high molecular weight (HMW) fraction, wherein the number average molecular weight (Mn) of the HMW fraction is at least 50 kg / mol when measured by gel permeation chromatography (GPC), and wherein the HMW fraction comprises at least 35% by weight of ethylene and at least 30% by weight of α-olefin comonomer.

[0219] The low molecular weight fraction (LMW) fraction, wherein the Mn of the LMW fraction is from 4 kg / mol to 25 kg / mol, and wherein the LMW fraction comprises at least 50 wt% ethylene and at least 29 wt% α-olefin comonomer, and wherein the ratio of the Mn of the HMW fraction to the Mn of the LMW fraction is at least 5:1.

[0220] The multimodal elastomer has a density between 0.853 g / cc and 0.875 g / cc, a shear viscosity of less than 2,500 Pa-s at 100 rad / s, and a shear viscosity of less than 120,000 Pa-s at 0.1 rad / s.

[0221] 2. The multimodal elastomer according to claim 1, wherein the α-olefin monomer comprises a group selected from C3-C4. 12 One or more α-olefins.

[0222] 3. The multimodal elastomer according to any one of the preceding claims, wherein the α-olefin monomer is 1-octene.

[0223] 4. The multimodal elastomer according to any one of the preceding claims, wherein the weight percentage of the α-olefin monomer incorporated in the HMW fraction is greater than the weight percentage of the α-olefin monomer incorporated in the LMW fraction.

[0224] 5. The multimodal elastomer according to any one of the preceding claims, wherein the weight percentage of the α-olefin monomer in the HMW fraction is at least 4% greater than the weight percentage of the α-olefin monomer in the LMW fraction.

[0225] 6. The multimodal elastomer according to any one of the preceding claims, wherein the multimodal elastomer comprises 50 wt% to 85 wt% of the high HMW fraction.

[0226] 7. The multimodal elastomer according to any one of the preceding claims, wherein the multimodal elastomer has a shear viscosity of less than 60,000 Pa·s at 0.1 rad / s.

[0227] 8. The multimodal elastomer according to any one of the preceding claims, wherein the ratio of Mn in the HMW fraction to Mn in the LMW fraction is at least 8:1.

[0228] 9. A thermoplastic olefin comprising:

[0229] The multimodal elastomer according to any one of the preceding items; and

[0230] Polypropylene.

[0231] 10. The thermoplastic olefin according to claim 9, comprising additional elastomers, block composites, fillers, or combinations thereof.

[0232] 11. A method for preparing a multimodal elastomer, comprising:

[0233] Add at least one ethylene monomer, at least one α-olefin comonomer, a first catalyst comprising a biphenol complex, and a second catalyst comprising a complex with a defined geometry to the reactor system.

[0234] The multimodal elastomer is produced by solution polymerization at a temperature of at least 100°C.

[0235] The multimodal elastomer comprises a high molecular weight (HMW) fraction and a low molecular weight (LMW) fraction.

[0236] When measured by gel permeation chromatography (GPC), the number-average molecular weight (Mn) of the HMW fraction is at least 50 kg / mol, and the HMW fraction comprises at least 35 wt% ethylene and at least 30 wt% α-olefin comonomer, and the Mn of the LMW fraction is from 4 kg / mol to 25 kg / mol, and the LMW fraction comprises at least 50 wt% ethylene and at least 29 wt% α-olefin comonomer.

[0237] The multimodal elastomer comprises: a ratio of Mn in the HMW fraction to Mn in the LMW fraction of at least 5:1; a density between 0.853 g / cc and 0.875 g / cc; a shear viscosity of less than 2,500 Pa·s at 100 rad / s; and a shear viscosity of less than 120,000 Pa·s at 0.1 rad / s shear.

[0238] 12. The method according to claim 11, wherein the multimodal elastomer comprises 20% to 90% by weight of a high molecular weight (HMW) fraction.

[0239] 13. The method according to item 11 or 12, wherein the weight percentage of the α-olefin monomer in the HMW fraction is at least 4% greater than the weight percentage of the α-olefin monomer in the LMW fraction.

[0240] 14. The method according to any one of items 11 to 13, wherein the reactor system comprises a single reactor.

[0241] 15. The method according to any one of items 11 to 13, wherein the reactor system comprises two reactors.

Claims

1. A multimodal elastomer comprising a copolymer of ethylene and at least one α-olefin monomer, wherein the multimodal elastomer comprises: A high molecular weight (HMW) fraction of 20% to 90% by weight, wherein the number-average molecular weight (Mn) of the HMW fraction is at least 75 kg / mol when measured by gel permeation chromatography (GPC), and wherein the HMW fraction comprises at least 50% by weight ethylene and at least 40% by weight and less than 50% by weight α-olefin comonomer; and The low molecular weight fraction (LMW) fraction, wherein the Mn of the LMW fraction is from 4 kg / mol to 25 kg / mol, and wherein the LMW fraction comprises at least 50% by weight of ethylene and at least 29% by weight of α-olefin comonomer, and wherein the ratio of the Mn of the HMW fraction to the Mn of the LMW fraction is at least 5:

1. The multimodal elastomer has a density between 0.853 g / cc and 0.875 g / cc, a shear viscosity of less than 2,500 Pa-s at 100 rad / s, and a shear viscosity of less than 120,000 Pa-s at 0.1 rad / s.

2. The multimodal elastomer according to claim 1, wherein the α-olefin monomer comprises a group selected from C3-C4. 12 One or more α-olefins.

3. The multimodal elastomer according to claim 1, wherein the α-olefin monomer is 1-octene.

4. The multimodal elastomer according to claim 2, wherein the α-olefin monomer is 1-octene.

5. The multimodal elastomer according to any one of claims 1 to 4, wherein the weight percentage of the α-olefin monomer incorporated in the HMW fraction is greater than the weight percentage of the α-olefin monomer incorporated in the LMW fraction.

6. The multimodal elastomer according to any one of claims 1 to 4, wherein the weight percentage of the α-olefin monomer in the HMW fraction is at least 4% greater than the weight percentage of the α-olefin monomer in the LMW fraction.

7. The multimodal elastomer according to any one of claims 1 to 4, wherein the multimodal elastomer comprises 50 wt% to 85 wt% of the high HMW fraction.

8. The multimodal elastomer according to any one of claims 1 to 4, wherein the multimodal elastomer has a shear viscosity of less than 60,000 Pa·s at 0.1 rad / s.

9. The multimodal elastomer according to any one of claims 1 to 4, wherein the ratio of Mn in the HMW fraction to Mn in the LMW fraction is at least 8:

1.

10. A thermoplastic olefin comprising: The multimodal elastomer according to any one of the preceding claims; and Polypropylene.

Citation Information

Patent Citations

  • Catalytic Olefin Block Copolymers with Controlled Block Sequence Distribution

    US20080269412A1

  • Ethylene Based Polymer

    US20150337062A1

  • Polymerization Process for Producing Ethylene Based Polymers

    US20150337063A1

  • A Polymerization Process for Producing Ethylene Based Polymers

    US20150344602A1

  • Elastic substantially linear olefin polymers

    US5272236A